Exposure to Bisphenol AF disrupts sex hormone levels and vitellogenin expression in zebrafish. Issue 3 (12th September 2014) - Yang, Xiaoxi; Liu, Yuchen; Li, Jia; Chen, Minjie; Peng, Di; Liang, Yong; Song, Maoyong; Zhang, Jie; Jiang, Guibin
ABSTRACT: Bisphenol AF (BPAF) is widely used in food‐contact products, electronic devices, and as a cross‐linking reagent in fluoroelastomers. There are growing concerns about its toxicity and endocrine‐disrupting effects based on its structural similarity with bisphenol A (BPA). The endocrine‐disrupting effects of BPAF were studied by exposing 2‐month‐old zebrafish to 0, 0.05, 0.25, or 1 mg/L BPAF for 28 days and evaluating the effect on growth, histopathology, hormone levels, enzyme activity, and gene expression. The overall fitness was not significantly affected. There were no apparent alterations in the gills and intestine tissues of both sexes after BPAF exposure. However, exposure to 1 mg/L BPAF caused damage to the liver in the male fish, characterized by hepatocellular swelling and vacuolation. There was no obvious effect in the liver of female fish, suggesting that the hepatic toxicity of BPAF is gender dependent. Gonadal examination indicated that exposure to 1 mg/L BPAF caused induction of acellular areas in the testis and retardation of oocyte development in the ovary. BPAF exposure increased free triiodothyronine levels of females in a dose‐dependent manner. In males, the testosterone levels decreased in a concentration‐dependent manner. In contrast, estradiol levels increased in a concentration‐dependent manner and were significantly higher in males exposed to 1 mg/L BPAF compared with the controls. In females, 0.05 and 0.25 mg/L BPAF caused an increase in testosterone levels. Furthermore, the estradiol levels increased in females exposed to 0.05 and 1 mg/L. We observed an upregulation of hepatic vitellogenin in both sexes and significantly higher levels in males exposed to 1 mg/L BPAF and females exposed to 0.25 mg/L BPAF, suggesting that BPAF has an estrogenic activity. Our results indicate that BPAF is an endocrine‐disrupting chemical that exerts reproductive toxicity and estrogenic effects on zebrafish. © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 285–294, 2016.